Forensic homicidal strangulation in women: Case series and systematic literature review - Ginevra Malta; Maria Puntarello; Mauro Midiri; Tommaso D'Anna; Stefania Zerbo; Antonina Argo (Forensic Science International: Synergy)
This systematic review explores women's homicidal strangulation using PRISMA method. A total of 40 Google Scholar, 26 PubMed and 4 manual searching articles were analyzed, while other sources were excluded due to lack of full texts, irrelevance, or outdated content. Review highlights gender violence as an underestimated issue and provides a socio-demographic analysis. Diagnosing strangulation can be challenging, particularly in absence of visible asphyxial signs in the external examination. Judicial authorities' collaboration and reliance on circumstantial evidence are crucial in forensic investigations. Strangulation is statistically prevalent in sexually motivated crimes and employs various methods. We reported four different strangulation cases at the Institute of Forensic Medicine, University of Palermo, to emphasize findings, forensic characteristics, and interpretation difficulties. The primary goal of this review is to shed light on homicidal strangulation's specific characteristics, given its underreported nature, and to stress the importance of mechanical asphyxia in forensic differential diagnosis. Distinguishing strangulation from other asphyxial deaths is difficult, as is identifying potential third-party involvement. This review also aims to provide key indicators that assist forensic pathologists in differentiating strangulation from other asphyxial causes of death. Future perspectives highlight the use of specific protocols, using artificial intelligence (AI), and instrumental investigations to support forensic pathologists in performing differential diagnoses and providing compatibility assessments.